Prevention of osteoporotic refractures in regional Australia. (15th June 2017) - Davidson, Emily; Seal, Alexa; Doyle, Zelda; Fielding, Kerin; McGirr, Joe
Abstract: Objective: Clinical guidelines recommend that patients who sustain a minimal trauma fracture (MTF) should receive a bone mineral density (BMD) scan and bisphosphonate (or equivalent) therapy if diagnosed with osteoporosis. A pilot fracture liaison service (FLS) was implemented in regional NSW to improve adherence to the guidelines. Design: Prospective cohort study with an historical control. Setting: Primary care. Participants: Control ( n = 47) and cohort ( n = 93) groups comprised patients consenting to interview who presented with a MTF to the major referral hospital 4 months before and 12 months after FLS implementation respectively. Main outcome measures: Primary outcome measures were the rates of BMD scans and anti‐osteoporotic medication initiation/review after MTF. Hospital admission data were also examined to determine death and refracture rates for all patients presenting during the study period with a primary diagnosis of MTF within 3 years of their initial fracture. Results: Although there was no improvement in BMD scanning rates, the reported rate of medication initiation/review after fracture was significantly higher ( P < 0.05) in the FLS cohort. However, once adjusted for age, this association was not significant ( P = 0.086). There was a lower refracture rate during the cohort period ( P = 0.013), however, there were significantly more deaths ( P = 0.035) within 3 years of initial fracture. When deaths were taken into account via competing risk regression, patients in the cohort period were significantly less likely to refracture than those in the control period (Hazard ratio = 0.576, P = 0.032). Conclusions: A rurally based nurse‐led FLS was associated with modest improvement after MTF. Consideration should be given to ways to strengthen the model of care to improve outcomes.